Comportamiento agronómico y valor nutricional de la asociación del pasto king grass (Pennisetum Purpureum X Pennisetum Thiphoides) con dos leguminosas en tres tiempos de corte - Benítez Ricaurte, Alfredo Rolando (2014)
Research "Agronomic performance and nutritive value of pasture Association King Grass (Pennisetum purpureum x Pennisetum thiphoides) with two pulses in three cutting times” was performed on the 33 km of the route Santo Domingo - El Carmen, Province Manabi, with a geographical location at 0° 16 ' 11'' South Latitude and 79° 25' 26'' west longitude. Regarding the province is located northeast of its jurisdiction. The trial lasted 90 days considering objective: To evaluate the agronomic performance and nutritional value of the association of King Grass (Pennisetum purpureum x Pennisetum thiphoides) with two pulses in three cutting times. The results of the study variables have the combination (King Grass + kudzu / 75 days) was higher in leaf width, total weight DM yield and forage legume with 5.09 cm; 3424.38 and 2154.24 g kg/ha-1; combination (King Grass + kudzu / 60 days) than the other treatments in leaf length, leaf weight, root weight and total weight of legume legume with 1.28 cm; 14.03 g; 3.53 g and 5985.00 g. For the variable weight of legume foliage, King DM yield and total return Gras kg/ha-1 kg/ha-1 association (King Grass + Centrosema / 60 days) is better with a value of 70.19 g; 26372.01 and 28026.45 kg/ha-1. It also presents the most useful $ 1,328.51 and the best cost / benefit ratio with a margin of 18.25. In Microbiological analysis of soil can be seen that at 75 days a greater quantity of nitrogen fixer’s asymbiotic stands; also a significant contribution of nitrogen warns.